Kemampuan Menulis Teks Iklan Berdasarkan Struktur dan Kaidah Kebahasaan Siswa Kelas VIII SMPN 17 Mataram - Ramdhani, Suci; Nilawati Astini, Baiq; Rahmayani, Ika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The problem behind this research is that students' ability to write advertising texts is still low. This is caused by students' lack of interest in participating in learning and teachers' lack of creativity when delivering learning material, so that students experience difficulty in learning to write advertising texts. This research aims to determine students' ability to write advertising texts based on the structure and linguistic rules of class VIII students at SMPN 17 Mataram. This research uses quantitative descriptive research. The population of this research is class VIII C students of SMPN 17 Mataram. The sample in this research consisted of 20 students. Data collection uses Test/Assignment techniques and documentation techniques. Based on the results and discussion, it shows that class VIII C students at SMPN 17 Mataram based on structural aspects are in the Quite Capable (CM) category with an average score of 61. The number of students who obtained scores in the very capable category was 5 students, 2 students in the capable category, 5 students received the moderately capable category, 6 students received the less capable category, and 2 students received the incapable category. Furthermore, based on aspects of linguistic rules, it is in the Less Able (KM) category with an average score of 55.85. The number of students who obtained scores in the very capable category was 3 students. 3 students got scores in the capable category. 9 students were in the underprivileged category, and 5 students got grades in the underprivileged category.